2022
DOI: 10.3390/cancers14051173
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Absolute Count of Monocytes in Patients Carrying Hematological Neoplasms and SARS-CoV2 Infection

Abstract: Background: Clinical course of COVID-19 depends on several patient-specific risk factors, including immune function, that is largely compromised in cancer patients. Methods: We prospectively evaluated 120 adult consecutive patients (including 34 cases of COVID-19 breakthrough after two full doses of BNT162b2 vaccine) with underlying hematological malignancies and a SARS-CoV-2 infection, in terms of patient’s clinical outcome. Results: Among fully vaccinated patients the achievement of viral clearance by day 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This should be investigated in future studies, which can leverage the median values and ranges of the immune subsets analyzed here (Supplemental Table 4 ). In this regard, we and others have shown recently how immune profiling in blood was an independent prognostic factor of severe SARS-CoV-2 infection in individuals with and without blood cancer [ 23 26 ]. This becomes particularly relevant with the advent of BCMA-targeting bispecific antibodies, which deplete (tumor and normal) plasma cells and are associated with an increased incidence of infections [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This should be investigated in future studies, which can leverage the median values and ranges of the immune subsets analyzed here (Supplemental Table 4 ). In this regard, we and others have shown recently how immune profiling in blood was an independent prognostic factor of severe SARS-CoV-2 infection in individuals with and without blood cancer [ 23 26 ]. This becomes particularly relevant with the advent of BCMA-targeting bispecific antibodies, which deplete (tumor and normal) plasma cells and are associated with an increased incidence of infections [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies investigating the mortality rate of hematological malignancy patients after they were infected with COVID-19, the overall mortality rates were reported to be up to 40%. 2 , 5 , 7 , 9 , 17 , 21 , 22 Vijenthira et al 4 reviewed the outcomes of 3377 patients with hematological malignancies and COVID-19 in a systematic review and meta-analysis. They found a higher mortality risk in older and hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing treatment was defined as having the treatment within 30 days before COVID-19 diagnosis. 5,17 The laboratory parameters at the diagnosis of COVID-19 [leukocyte and platelet counts, lymphocyte percentage, C-reactive protein (CRP), and D-dimer] were investigated and categorized as low, normal, or high using each laboratory's lower and upper limits. In addition, we categorized the treatment modalities for hematological malignancies as conventional chemotherapy, targeted therapies (small-molecule inhibitors and monoclonal antibodies), immunotherapy (checkpoint inhibitors), and immunomodulatory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an earlier study showed that patients with COVID-19 (including 90 patients with multiple myeloma with a prior history of autologous and allogeneic hematopoietic stem-cell transplantation (HSCT) have poor overall survival 18 . Interestingly, a recent study by Romano et al (2022) showed that absolute monocyte count prior to SARS-CoV-2 infection is predictive of the risk of overall survival in patients with heme malignancies 19 . Next, we focused on drug classes commonly used as anti-myeloma therapies.…”
Section: Discussionmentioning
confidence: 99%